Production of free radicals and catalase activity during acute exercise training in young men - de Castro, M. A. C.; Cavalcanti Neto, F. F.; Lima, L. M. C.; da Silva, F. M.; de Oliveira, R. J.; Zanesco, A. (Biology of Sport, 2009)
Reactive oxygen species (ROS) are constantly produced by cells that promote cellular oxidative damage and are neutralized by an antioxidant system including superoxide dismutase, glutathione, peroxidase and catalase. Male volunteers were exercised for 20 minutes, three days (60, 70 and 80% of maximum heart rate). Catalase activity and plasma malondialdehyde concentration were measured. The mean age of the volunteers was 25±7 years, with body mass index of 24.03 4.32 kg/m2. Acute exercise training produced an increase of malondialdehyde concentration that was exercise intensity-dependent in young volunteers. However, catalase activity shows a great variability at baseline and the percentual of reduction was exercise intensity-independent in this particular population. Therefore, our study shows that acute cycling exercise promotes an increase of oxidative stress that was exercise intensity-dependent in young volunteers. Furthermore, the antioxidant system measured by catalase activity was effective to counterbalance the ROS production showing a saturation behavior at an intensity of 70 % of maximum heart rate.